Design of a new class of broad-spectrum therapeutics targeted to drug-resistant bacteria - Amrutha Surendran; Agnes Turnbull; Allen Flockhart; Fern Findlay-Greene; Martyna Nowosielska; Donald Morrison; David J. Mincher; Samantha Donnellan (All Life)
We hypothesise that antimicrobial resistance (AMR) cannot be overcome by simply ‘drugging’ single biological targets, therefore, our focus is developing broad-spectrum therapeutics. Herein we present the synthesis of two novel spacer-linked, anthraquinone-triphenylphosphonium (AQ-TPP) conjugates (4) and (5) as early lead compounds in a new class of agent designed to penetrate the lipophilic barriers of the membranes of a diverse family of species; and establish bacterial growth inhibitory properties against methicillin-resistant Staphylococcus aureus (NCTC 13616) and Mycobacterium smegmatis [mc2155] (as a surrogate for Mycobacterium tuberculosis). The MIC and MBC values of (4) and (5) were determined against MRSA and found to be equipotent [MIC for each: 1 µg/mL (1.2 µM)]. Whereas the amide-linked conjugate (5) was determined to have 2-fold greater bactericidal potency [MBC 1 µg/mL (1.2 µM] than ester-linked (4). The anthraquinone-TPP conjugates (4) and (5) were active in vitro against Mycobacterium smegmatis (graphical abstract) and were equipotent as determined by their MIC values; in contrast to MRSA, the less hydrophobic (4) had 2-fold greater bactericidal potency than (5) as measured by their MBC values. Notably, both conjugates showed potent intracellular growth inhibitory activity in infected THP-1 macrophages. The conjugates are promising leads for the development of new antibacterial drugs. Key policy highlights Development of a novel class of antimicrobial compounds Drug screen against a WHO ‘high’ priority drug-resistant pathogen that poses the greatest threat to human health (methicillin-resistant Staphylococcus aureus) Drug screen against a surrogate for Mycobacterium tuberculosis, one of the leading causes of mortality worldwide.